Diversity and distribution of crustaceans in the mangrove forest of Nusa Lembongan, Bali, Indonesia - I KETUT GINANTRA; I KETUT MUKSIN; MARTIN JONI; I MADE SAKA WIJAYA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Ginantra IK, Muksin IK, Joni M, Wijaya IMS. 2023. Diversity and distribution of crustaceans in the mangrove forest of Nusa Lembongan, Bali, Indonesia. Biodiversitas 24: 4533-4541. Research on the diversity and distribution of crustaceans in the mangrove forest of Nusa Lembongan, Bali, Indonesia was conducted from March to June 2022. Sampling was carried out using the quadratic method at seven mangrove forest sites. The identification of crustacean species is based on morphological characteristics, namely carapace color, claw shape, legs, and body size. Crustacean density was determined based on the number of individuals per unit area of mangrove forest, diversity was determined by the Shanon-Wiener Index, and crustacean distribution was determined based on the frequency of species presence in each square at the seven study sites. Environmental factors were also measured: Mangrove vegetation, substrate type, temperature, pH, and salinity. The results showed that 12 species of crustaceans were found, consisting of 10 species of crabs and two species of hermit crabs. Several species of crabs are quite dominant in the mangroves of Nusa Lembongan namely Sesarma pictum (De Haan, 1835), with a density of 7 individuals/5 m2, Uca tetragonon (Herbst, 1790) of 3.7 individuals/5 m2, Uca rosea (Tweedie, 1837) with a density of 2.5 individuals/ 5 m2, and Uca triangularis (A. Milne-Edwards, 1873) with a density of 2 individuals/5 m2. Environmental factors support the life of Nusa Lembongan crustaceans, namely the type of substrate, mostly muddy and sandy, diverse species of mangrove plants, both true and associated mangroves, water temperature 27.70-29.00°C, pH 6.88-7.15 and water salinity ranging from 27.83-31.53‰. Crustacean diversity is included in the moderate category with their diversity index. There are three crab species with moderate to frequent (absolute) frequency of presence, namely U. rosea (Fi: 57.15%), S. pictum (Fi: 71.43%), and U. tetragonon (Fi: 85.71%). These species are present in four to six mangrove forest sites.